Tesnostične pregrade v našem telesu - Jezernik, Kristijan (Medicinski razgledi, 2010)
Tight junctions comprise a crucial part of epithelial barriers by forming a molecular pore like structure that encircles the apex of individual cells. They control the passage of small molecules between apical and basolateral compartments. Junctions are composed of a branching network of sealing strands. Each strand is formed from a row of transmembrane proteins namely occludin and claudins, embedded in both plasrna membranes, with extracellular domains joining one another direcdy. These associate with different peripheralmembrane proteins located on the intracellular side of plasrna membrane, which anchor the strands to the actin cytoskeleton. This overview gives a detailed survey about the proteins associated with tight junctions, their structure and functions including a wealth of the relevant literature. We summarize our knowledge about tight junction proteins in mammalian epithelial tisue and their involvement in some diseases. Their putative suitability as new targets for improving drug delivery is discussed.
Keywords: Tesni stiki; Tight Junctions; Mikrovlakno, beljakovine; Membrane Proteins; Membranske beljakovine; Membrane Potentials; Membranski potenciali; Microfilament Proteins; Rana, celjenje; Wound Healing; Celična membrana, propustnost; Cell Membrane Permeability; Kapilarna propustnost; Capillary Permeability; citologija; fiziologija; tesni stik; celična membrana